2001
DOI: 10.1093/gerona/56.7.m438
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Sway Measures of Postural Stability During Clinical Balance Tests: Effects of Age

Abstract: Accurate measurement of trunk angular sway during stance and gait tasks provides a simple way of reliably measuring changes in balance stability with age and could prove useful when screening for balance disorders of those prone to fall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
176
1
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(199 citation statements)
references
References 27 publications
10
176
1
12
Order By: Relevance
“…However, Paulus et al found that visual stabilization decreases with increasing distances to steady visual targets (Paulus et al 1984). In this study, we observed that vision only significantly reduced the body movements and EMG activity while standing on foam, which concurs with findings in other foam studies (Brandt 1991;Gill et al 2001;Allum et al 2002;Blackburn et al 2003) This supports previous studies showing that unreliable information from the somatosensory receptors increases the reliance on visual and/or vestibular inputs in postural control (Brandt 1991;Rosengren et al 2007). Moreover, spectral separation analysis showed that vision …”
Section: Effect Of Foam Support Surface and Visionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, Paulus et al found that visual stabilization decreases with increasing distances to steady visual targets (Paulus et al 1984). In this study, we observed that vision only significantly reduced the body movements and EMG activity while standing on foam, which concurs with findings in other foam studies (Brandt 1991;Gill et al 2001;Allum et al 2002;Blackburn et al 2003) This supports previous studies showing that unreliable information from the somatosensory receptors increases the reliance on visual and/or vestibular inputs in postural control (Brandt 1991;Rosengren et al 2007). Moreover, spectral separation analysis showed that vision …”
Section: Effect Of Foam Support Surface and Visionsupporting
confidence: 93%
“…Several studies that have used a foam support surface show that trunk movements increase significantly in patients with balance deficits (Gill et al 2001;Allum et al 2002;Blackburn et al 2003). Our study, showing that healthy subjects also increased their hip and shoulder movements while standing on a compliant foam surface, confirms that assessment of trunk movements can provide essential information about postural control.…”
Section: Effect Of Foam Support Surface On the Multi-segmented Body Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The TWT test has been utilized as the dynamic walking balance component of several validated test batteries regarding fall prediction in the elderly, such as the Fullerton Advanced Balance Scale [3,4], the LIFE pilot study protocol [5], Good Walkers Test [6], and the EPIDOS Prospective Study balance protocol [7]. The TWT has been utilized as a test of dynamic walking balance to determine gait stability and pathological quantification including prediction of falls in the elderly population [3,9,[34][35][36][37][38][39][40], diagnose ataxia and other vestibular disorders [29,41], test for vertigo [42], tropical ataxic neuropathy [43], traumatic brain injury [40], peripheral neuropathy [44], and functional mobility [45][46][47][48]. The TWT is considered a clinically efficacious test of dynamic balance in medical text books [29,49] and for research purposes [2,50].…”
Section: Introductionmentioning
confidence: 99%
“…Recientemente, se han incorporado sistemas portátiles de registro basados en la acelerometría, que incorporan varios ace-lerómetros triaxiales que actúan como múltiples sensores para medir aceleraciones gravitacionales e inerciales, aplicables al estudio del movimiento [30][31][32] . Estos sistemas, que podrían ser considerados de alto techo en base a la calidad de la información proporcionada, han supuesto un gran avance, al posibilitar estudios fuera del laboratorio.…”
Section: Envejecimiento Fragilidad Y Capacidad Funcionalunclassified